The Concept of Competency-Based Islamic Religious Education Curriculum Planning in Schools and Madrasas - Shelvia Loviana; Umi Afifah; Eti Hadiati; Sovia Mas Ayu; Ahmad Fauzan (al-Afkar, Journal For Islamic Studies, 2025)
This article is focused on describing the concept of competency-based Islamic religious education curriculum planning in schools and madrasas. This competency curriculum planning discussion aims to direct students towards the expected behavioral changes. The planning process involves determining goals and making decisions that will be realized in the form of activities or actions that focus on the future. This study uses a literature study design with a philosophical approach. The data analysis technique used is analytical technique, namely drawing conclusions about objects, both from thoughts, systematic images and factual in nature. The results of this study indicate that competency-based curriculum planning for Islamic Education (PAI) focuses on achieving students' competencies comprehensively, encompassing cognitive, affective, and psychomotor aspects. This curriculum not only emphasizes mastery of subject matter but also fosters tangible behavioral changes and the development of relevant life skills. The expected competencies include critical thinking skills, social abilities, and the internalization of spiritual and moral values. Moreover, competency-based curriculum planning is characterized by clear concepts, a holistic approach, and a systematic framework. Learning objectives are formulated as observable and measurable behaviors, enabling accurate evaluation of educational outcomes. This study also highlights the importance of involving all components of the learning process, including educators, students, materials, methods, evaluations, institutional managers, and other educational resources. Therefore, competency-based curriculum design provides clear direction for PAI learning, ensuring the achievement of educational goals that support the development of students’ character as individuals who are faithful, knowledgeable, and morally upright.